2019
DOI: 10.1016/j.abb.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

TFAM overexpression diminishes skeletal muscle atrophy after hindlimb suspension in mice

Abstract: The present study aims to investigate if overexpressing the mitochondrial transcription factor A (TFAM) gene in a transgenic mouse model diminishes soleus and gastrocnemius atrophy occurring during hindlimb suspension (HLS). Additionally, we aim to observe if combining exercise training in TFAM transgenic mice prior to HLS has a synergistic effect in preventing skeletal muscle atrophy. Male C57BL/6J-based transgenic mice (12-14 weeks old) overexpressing TFAM were assigned to a control (T-Control), 7-day HLS (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…SIRT2 is reported to modulate skeletal muscle atrophy by inhibiting excessive autophagy [ 27 ] and improve myotube differentiation and hypertrophy [ 28 ]. Enhanced mitochondrial function is conducive to improving muscle atrophy [ 29 ], while the reduction of mitochondrial biogenesis and oxidative phosphorylation leads to the production of ROS, which causes excessive muscle protein degradation [ 30 ]. Mitochondrial transcription factor A (TFAM) binds and coats mtDNA, protecting it from ROS-induced degradation and maintaining mitochondrial function [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT2 is reported to modulate skeletal muscle atrophy by inhibiting excessive autophagy [ 27 ] and improve myotube differentiation and hypertrophy [ 28 ]. Enhanced mitochondrial function is conducive to improving muscle atrophy [ 29 ], while the reduction of mitochondrial biogenesis and oxidative phosphorylation leads to the production of ROS, which causes excessive muscle protein degradation [ 30 ]. Mitochondrial transcription factor A (TFAM) binds and coats mtDNA, protecting it from ROS-induced degradation and maintaining mitochondrial function [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the enzymes of the mitochondrial electron transport chain, Complex II and Complex IV participate in the production of the vast majority of cellular energy. In addition, TFAM is involved in mitochondrial biogenesis which is activated by PGC-1α and coats mtDNA, protecting against ROS exposure. , The overexpression of TFAM could alleviate aging and obesity-induced muscle atrophy . Here, we found that the decreased expression of TFAM, Complex II, and Complex IV caused by obesity was upregulated by AR-C17 administration in both PA-induced C2C12 cells and obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mitophagy is proven to improve mitochondrial function in skeletal muscle . Inhibition of mitophagy proteins such as Beclin-1, P62, and LC3 could affect the production of lysosomes, which generate the small molecules reutilized by cells to produce new healthy mitochondria. , According to recent studies, poor autophagy flux and downregulated level of mitophagy-related proteins such as Beclin-1 and P62 are detected in aging skeletal muscle . In addition, knockdown of Parkin causes damaged mitochondrial quality and decreased mtDNA number and oxidative phosphorylation level, while overexpression of Parkin improves muscle mass and exercise capacity in atrophied skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in or complete abolishment of TFAM have been associated with marked decreases in mtDNA, leading to profound skeletal muscle wasting [ 163 ]. The important role of TFAM in preservation of muscle mass is underlined by the fact that TFAM overexpression has been shown to protect from hindlimb suspension-induced muscle wasting [ 164 ]. In contrast, in survivors of critical illness, an upregulation in the mRNA of PGC1α, NRF1 and TFAM could be indicative of ongoing repairing processes or, on the other hand, could serve as a mechanism of resilience [ 82 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%